Outsourcing with distributed teams in large-scale environments - Camara, Rafael; Marinho, Marcelo; Sampaio, Suzana; Honório, Ivaldir; Moura, Hermano (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
Outsourcing projects continue to grow through a more distributed and connected environment among teams from all over the globe. Due to it, many customer-vendor relationships are being formed in multi-site settings around a large-scale agile project. Companies are constantly looking for suppliers to assist and develop their complex products, although large-scale agile projects with many teams require some attention to the outsourcing project. Based on it, this study aims to conduct a systematic literature review regarding how outsourced distributed teams from large-scale agile projects are handling their operation. From 23 studies, it was possible to synthesize six distinct themes and 15 patterns of outsourcing distributed teams working in large-scale contexts.